2022
DOI: 10.3390/biomedicines10030599
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of Multiple System Atrophy: An Update

Abstract: Multiple system atrophy (MSA) is a fatal, rapidly progressing neurodegenerative disease of uncertain etiology, clinically characterized by various combinations of Levodopa unresponsive parkinsonism, cerebellar, autonomic and motor dysfunctions. The morphological hallmark of this α-synucleinopathy is the deposition of aberrant α-synuclein in both glia, mainly oligodendroglia (glial cytoplasmic inclusions /GCIs/) and neurons, associated with glioneuronal degeneration of the striatonigral, olivopontocerebellar an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 169 publications
(217 reference statements)
0
11
0
Order By: Relevance
“…Interestingly, VBM did not show a significant progression of SN atrophy over time, and therefore, the T1w/T2w ratio, with a 30% variation at 1-year follow-up, could be an MRI parameter more sensitive to change in this brain area. The rationale for studying SN resides in its involvement in MSA as known by neuropathological studies ( 27 , 28 ). In fact, regional neurodegeneration in SN as assessed by neuromelanin-sensitive MRI does not differ between MSA and PD, and the T1w/T2w ratio in SN has been recently proposed as a novel parsimonious biomarker in the PD population ( 15 ).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, VBM did not show a significant progression of SN atrophy over time, and therefore, the T1w/T2w ratio, with a 30% variation at 1-year follow-up, could be an MRI parameter more sensitive to change in this brain area. The rationale for studying SN resides in its involvement in MSA as known by neuropathological studies ( 27 , 28 ). In fact, regional neurodegeneration in SN as assessed by neuromelanin-sensitive MRI does not differ between MSA and PD, and the T1w/T2w ratio in SN has been recently proposed as a novel parsimonious biomarker in the PD population ( 15 ).…”
Section: Discussionmentioning
confidence: 99%
“…37 Similarly, fluctuating cognition seems to be absent in other neurodegenerative movement disorders such as MSA. 50 This symptom is defined as "alternating episodes of normal or almost normal function with periods of impaired cognitive performance, inattention, and excessive daytime drowsiness with transient confusion on waking." 51…”
Section: Dementia With Lewy Bodiesmentioning
confidence: 99%
“…57 Since that time, however, several longitudinal studies have shown some MSA patients can eventually experience cognitive impairments. 57 For instance, approximately one-third of patients reference memory complaints, 50,58 and one study of 59 patients diagnosed with probable MSA reported an eventual dementia prevalence of 15% over the course of the disease (nine probable MSA patients with a disease duration of 5.2 AE 2.3 years). 59 The deficits mainly affect performance in executive function, attention, and memory.…”
Section: Multiple System Atrophymentioning
confidence: 99%
“…Recently, accumulating evidence suggests the existence of distinct strains of α-syn, possibly because of genetic polymorphism or protein modification, and their association with different patterns of disease propagation and atrophic regions [ 47 ]. Interestingly, several studies have indicated that α-syn derived from GCIs of MSA has more potent activity than that from Lewy bodies of PD [ 47 , 48 ]. The diversity of seeding propensities of α-syn in different brain regions supports the notion of the clinical and morphological heterogeneity of MSA as well as clinical difference between MSA and PD/LBD [ 41 , 49 ].…”
Section: An Overview Of Msamentioning
confidence: 99%